Early Time-Dependent Dynamic Changes of TBET and GATA3 mRNA Expressions in Patients with Acute Coronary Syndrome. Issue 5 (30th September 2013) - Rainer, Timothy H.; Graham, Colin A.; Chan, Rebecca W. Y.; Chan, Cangel P. Y.; Tan, Patrick C. F.; Yip, Gabriel W. K.; Yu, Cheuk-Man
Abstract : Background . T-box expressed in T cells (TBET) and guanine adenine thymine adenine sequence-binding protein 3 (GATA3) play important roles in the differentiation of Th1 and Th2 subsets, which contributes to the progression of acute coronary syndrome (ACS). Objective . This study aimed to investigate the temporal change of TBET/GATA3 mRNA ratio in ACS. Methods . Thirty-three patients suspected of ACS with symptom onset within 24 hours were recruited. Blood samples were taken after arrival at the emergency department and at hourly intervals until the 6th hour. The mRNA expressions of TBET and GATA3 were quantified by a real-time RT-qPCR. Results . The TBET/GATA3 mRNA ratio was elevated dramatically in patients with acute myocardial infarction (AMI) and exhibited biphasic M-shaped release kinetics with two distinct peaks. The ratio was elevated 2 hours after symptom onset, dropped to the lowest level at 10 hours, and rose to the second peak at 14 hours. A similar biphasic M-shaped curve was observed in AMI patients with blood samples taken prior to any intervention. Conclusions . The TBET/GATA3 mRNA ratio was elevated in AMI patients throughout most of the first 20 hours after symptom onset. The biphasic M-shaped release kinetics was more likely to reflect pathophysiological changes rather than treatment effects.